Deforestation for agriculture leads to soil warming and enhanced litter decomposition in subarctic soils - Peplau, Tino; Poeplau, Christopher; Gregorich, Edward; Schroeder, Julia (Biogeosciences, 2023)
The climate-change-induced poleward shift of agriculture could lead to enforced deforestation of subarctic forest. Deforestation alters the microclimate and, thus, soil temperature, which is an important driver of decomposition. The consequences of land-use change on soil temperature and decomposition in temperature-limited ecosystems are not well understood. In this study, we buried tea bags together with soil temperature loggers at two depths (10 and 50 cm) in native subarctic forest soils and adjacent agricultural land in the Yukon Territory, Canada. A total of 37 plots was established on a wide range of different soils and resampled after 2 years to quantify the land-use effect on soil temperature and decomposition of fresh organic matter. Average soil temperature over the whole soil profile was 2.1 ± 1.0 and 2.0 ± 0.8 ∘C higher in cropland and grassland soils compared to forest soils. Cumulative degree days (the annual sum of daily mean temperatures > 0 ∘C) increased significantly by 773 ± 243 (cropland) and 670 ± 285 (grassland). Litter decomposition was enhanced by 2.0 ± 10.4 % and 7.5 ± 8.6 % in cropland topsoil and subsoil compared to forest soils, but no significant difference in decomposition was found between grassland and forest soils. Increased litter decomposition may be attributed not only to increased temperature but also to management effects, such as irrigation of croplands. The results suggest that deforestation-driven temperature changes exceed the soil temperature increase that has already been observed in Canada due to climate change. Deforestation thus amplifies the climate–carbon feedback by increasing soil warming and organic matter decomposition.